Fertilization management strategies for 'Agata' potato production - Soratto, Rogerio P. [UNESP]; Yagi, Renato; Job, Andre Luiz G. [UNESP]; Fernandes, Adalton M. [UNESP] (Assoc Brasileira Horticultura, 2021)
Fluctuations in potato prices and invariably rising production costs need sustainable fertilization strategies. For this purpose, two experiments were conducted in the southwestern region of Sao Paulo state to evaluate fertilization management strategies for the 'Agata' potato cultivar. The treatments consisted of the producer's standard fertilization (1700 kg ha(-1) NPK 4-30-10 at planting + 100 kg ha(-1) urea and 150 kg ha(-1) KCl at hilling) and combinations of two P rates at planting (standard rate and half of the rate), as monoammonium phosphate (MAP) with two forms of KCl application (total rate in the post-planting phase or half of the rate in the post-planting phase and half at hilling). The application of half the P rate (255 kg ha(-1) P2O5) as the MAP at planting and the transfer of K from planting to applications in the post-planting phase or in the post-planting phase and at hilling, despite having provided a lower leaf P concentration, maintained the total tuber yield with higher operational yield of planting fertilization. It also increased the yield of tubers with a diameter >4.5 cm under conditions of lower water availability in the vegetative stages of the crop and soil with medium availability of P and K. Such a fertilization strategy is valuable for cost reductions and possible environmental liabilities.
Keywords: Solanum tuberosum; monoammonium phosphate; mineral nutrition; tuber yield; tuber dry matter